Self-healing temperature-control anti-crack waterproof material for concrete and preparation method of self-healing temperature-control anti-crack waterproof material

By using self-healing temperature-controlled crack-resistant and waterproof materials in concrete, the cracking problem caused by hydration heat and volume shrinkage of concrete is solved, reducing shrinkage, improving density and self-healing ability, thereby improving the concrete structure. Crack resistance, water resistance and durability.

CN119330630APending Publication Date: 2025-01-21CHINA RAILWAY FIRST SURVEY & DESIGN INST GRP

Patent Information

Application Number
CN202411515140.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The hydration heat generated by concrete during hydration and volume shrinkage cause cracking problems, resulting in reduced durability, safety and aesthetics of the building.

Method used

A self-healing temperature-controlled anti-cracking waterproof material is used. The material is composed of expansion components, temperature-control components, active components, self-healing components, moisturizing components and plasticizing components. Through infiltration crystallization technology Comprehensively and systematically solve the problem of concrete cracking.

Benefits of technology

This material can significantly reduce the temperature shrinkage, autogenous shrinkage and full-cycle compensation shrinkage of concrete, improve the compactness and self-healing ability of concrete, thereby comprehensively improving the crack resistance, waterproofing and long-term durability of the concrete structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330630A_ABST
    Figure CN119330630A_ABST
Patent Text Reader

Abstract

The invention discloses a self-healing temperature-control anti-crack waterproof material for concrete and a preparation method of the self-healing temperature-control anti-crack waterproof material. The reasons for causing concrete cracking mainly comprise a load effect and a shrinkage effect. The skin care composition comprises 40%-70% of an expansion component, 1%-3% of a temperature control component, 5%-10% of an active component, 5%-10% of a self-healing component, 10%-20% of a moisturizing component and 5%- Cracking caused by self-shrinkage, temperature shrinkage, drying shrinkage, insufficient compactness and the like of a concrete structure is improved, and the problem of cracking of concrete is comprehensively and systematically solved with the assistance of a capillary crystallization technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building material concrete admixtures, and specifically relates to a self-healing temperature-controlling, crack-resistant and waterproof material for concrete and a preparation method thereof. Background Art

[0002] As the main material in today's construction industry, concrete has many advantages, such as easy raw material availability, simple preparation, low cost, convenient construction, and high compressive strength. However, the hydration heat and volume shrinkage of cement, the key cementitious material, during the hydration process can cause cracking, which cannot be ignored. The cracking of concrete structures will significantly reduce the durability, safety, and aesthetics of buildings. Therefore, how to effectively solve the cracking problem of concrete is a common concern in the engineering community.

[0003] Research shows that the main causes of concrete cracking include load and shrinkage, of which cracking caused by shrinkage accounts for more than 80%. Therefore, how to reduce concrete shrinkage is an important direction to solve the generation of engineering cracks. Concrete shrinkage includes: plastic shrinkage, autogenous shrinkage, temperature shrinkage, carbonization shrinkage and drying shrinkage, etc., and today's concrete engineering tends to be large-structured and large-sized. For large-volume structural concrete, temperature shrinkage and autogenous shrinkage are the main causes of shrinkage. Therefore, starting from the above two aspects is the main direction to solve the cracking of concrete structures. At the same time, the occurrence of cracks in concrete structures is inevitable. How to reduce the risk of cracks and self-repair the cracks is the direction of technological development.

[0004] Patent No. CN 116514451A discloses a self-healing inorganic nano anti-crack and permeability reducing agent, which is mainly composed of key components such as sodium methyl silicate, hydration heat inhibitor, self-healing active component, shrinkage reducing agent, etc. It has a certain self-healing effect, but its hydration heat inhibitor is mainly a conventional retarder, which cannot play a good temperature control effect and cannot compensate for concrete shrinkage.

[0005] Patent No. CN 116621499A discloses a self-healing antifreeze, rust and cracking agent, the main components of which include sodium silicate, reaction accelerator, antifreeze compacting agent, rust inhibitor, ion complexing agent, waterproofing agent, etc. The industrialization of this technical solution is relatively complex and costly, and it is unable to control the internal temperature of concrete and compensate for shrinkage, and cannot fundamentally solve the problem of concrete cracking. Summary of the invention

[0006] In order to make up for the shortcomings of the prior art, the present invention provides a self-healing temperature-controlling, crack-resistant and waterproof material for concrete and a preparation method thereof, which improves the cracking of concrete structures caused by autogenous shrinkage, temperature shrinkage, drying shrinkage, insufficient density, etc., and is supplemented by penetration crystallization technology, thereby comprehensively and systematically solving the cracking problem of concrete.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A self-healing temperature-controlling, anti-cracking and waterproof material for concrete, characterized by comprising 40% to 70% expansion components, 1% to 3% temperature-controlling components, 5% to 10% active components, 5% to 10% self-healing components, 10% to 20% moisture-retaining components and 5% to 10% plasticizing components.

[0009] Furthermore, the expansion component consists of a carbonized modified magnesium oxide expansion agent and calcium oxide-calcium sulphoaluminate.

[0010] Furthermore, the temperature control component is prepared by acidification treatment of modified starch, wherein the modified starch is at least one of oxidized starch, starch ester, starch ether, cross-linked starch, grafted starch, cyclodextrin, white dextrin, and dialdehyde starch; and the acid-treated material includes at least one of formic acid, acetic acid, oxalic acid, malonic acid, and tartaric acid.

[0011] Furthermore, the active component is prepared by uniformly mixing low-temperature alumina and CSH gel nanocrystalline cores.

[0012] Furthermore, the self-healing component is prepared by uniformly mixing an accelerator and a main material in a ratio of 1:5 to 1:9; the main material is a silicate, including at least one of sodium silicate, potassium silicate, lithium silicate, and magnesium silicate; the accelerator is an aminocarboxylate, including at least one of sodium nitrilotriacetate, sodium ethylenediaminetetraacetate, and sodium diethylenetriaminepentacarboxylate.

[0013] Furthermore, the moisturizing component is ultra-fine rice husk ash.

[0014] Furthermore, the plasticizing component is a mixture of glass microsphere powder and polycarboxylic acid water reducer in a ratio of 4:1 to 9:1.

[0015] Furthermore, it includes 15-35% of carbonized modified magnesium oxide expansion agent, 25-45% of carbonized modified calcium oxide-calcium sulfoaluminate expansion agent, 1-3% of acidified modified starch, 1-3% of low-temperature alumina, 4-8% of CSH gel nanocrystalline core, 4.5-9% of sodium silicate, 0.5-1.5% of sodium ethylenediaminetetraacetate, 10-20% of ultrafine rice husk ash, 3.5-8% of vitrified microsphere powder, and 0.5-2% of polycarboxylic acid water reducer.

[0016] Furthermore, it includes 25% of carbonized modified magnesium oxide expander, 35% of carbonized modified calcium oxide-calcium sulfoaluminate expander, 2% of acidified modified starch, 2% of low-temperature alumina, 5% of CSH gel nanocrystalline core, 6% of sodium silicate, 1% of sodium ethylenediaminetetraacetate, 15% of ultrafine rice husk ash, 8% of vitrified microsphere powder, and 1% of polycarboxylic acid water reducer.

[0017] A preparation method of a self-healing temperature-controlling, anti-cracking and waterproof material for concrete, characterized in that carbonized modified magnesium oxide expansion agent, carbonized modified calcium oxide-calcium sulfoaluminate expansion agent, acidified modified starch, low-temperature alumina, CSH gel nanocrystalline core, silicate, aminocarboxylate, ultrafine rice husk ash, vitrified microbead powder and polycarboxylate water reducer are uniformly mixed in a certain proportion to obtain the self-healing temperature-controlling, anti-cracking and waterproof material.

[0018] Beneficial effects of the present invention:

[0019] 1) After the self-healing temperature-controlling, anti-cracking and waterproof material is added to the present invention, the workability of concrete can be improved, the density of concrete can be improved, the heat release rate of cement hydration can be reduced, the peak temperature can be significantly reduced, the generation of temperature cracks can be effectively reduced, and the mechanical properties of concrete at all ages can be improved, so that the 7d compressive strength ratio is ≥105%, the 28d compressive strength ratio is ≥110%, and the 60d compressive strength ratio is ≥110% compared with the control group;

[0020] 2) The self-healing temperature-controlling, anti-cracking and waterproof material of the present invention can generate large expansion energy during the hydration process, with small loss of expansion energy in the concrete plastic stage, obvious shrinkage compensation effect in the cooling stage, and sustainable compensation for concrete shrinkage, effectively reducing the risk of structural shrinkage cracking;

[0021] 3) The self-healing temperature-controlling, crack-resistant and waterproof material of the present invention has good adaptability to various cements, cementitious materials, admixtures and ambient temperatures. In high-temperature seasons, the material has an obvious temperature-controlling effect and a continuous and stable shrinkage compensation effect;

[0022] 4) The self-healing temperature-controlling and anti-cracking waterproof material of the present invention has an obvious self-repairing effect on concrete materials under the synergistic effect of modified magnesium oxide, self-healing main materials and their accelerators, and the secondary water permeability pressure ratio is greater than 200%;

[0023] 5) The self-healing temperature-controlling, anti-cracking and waterproof material of the present invention can effectively reduce the temperature shrinkage, self-shrinkage and full-cycle compensatory shrinkage of concrete, and improve the density of concrete, and the self-healing ability is significantly enhanced. From the perspectives of anti-cracking, density, self-healing and other dimensions, the anti-cracking, waterproof and long-term durability of concrete structures are comprehensively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a diagram showing the development law of the concrete restricted expansion rate at different curing temperatures according to the present invention. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with specific implementation modes.

[0026] The self-healing temperature-controlling, crack-resistant and waterproof material for concrete of the present invention comprises 40% to 70% of expansion components, 1% to 3% of temperature-controlling components, 5% to 10% of active components, 5% to 10% of self-healing components, 10% to 20% of moisture-keeping components and 5% to 10% of plasticizing components.

[0027] Specifically, the expansion component is composed of a carbonization-modified magnesium oxide expansion agent and a calcium oxide-calcium sulfoaluminate dual expansion source expansion agent in a mass ratio of 1:1 to 1:2, and the MgO content is greater than 85wt%. The magnesium oxide is one of the R type, M type or S type specified in the standard CBMF 19-2017 "Magnesium oxide expansion agent for concrete", and is prepared by carbonic acid modification; the calcium oxide-calcium sulfoaluminate dual expansion source expansion agent meets the technical index requirements of type II in GB / T 23439-2017 "Concrete expansion agent". The modified calcium oxide-calcium sulfoaluminate is prepared by carbonization modification, and the fineness is controlled to be 0.08 to 0.2mm.

[0028] After modification, the hydration activity of magnesium oxide can be further delayed, which can compensate for the later shrinkage of concrete. Some unhydrated modified magnesium oxide also has a certain self-healing effect. After carbonization modification and particle optimization, the calcium oxide-calcium sulfoaluminate expansion agent can not only significantly reduce its loss of expansion energy in the plastic stage of concrete, but also increase the effect of compensating for shrinkage in the cooling stage, and improve the influence of temperature on the loss of expansion energy of calcium expansion agent. It overcomes the problem that the effect of calcium expansion agent in compensating for shrinkage is not obvious under conditions of high temperature in summer or increased temperature inside concrete, realizes full-cycle compensation for concrete shrinkage, and reduces the risk of structural cracking.

[0029] The temperature control component is prepared by acid treatment of modified starch, and the modified starch is at least one of oxidized starch, starch ester, starch ether, cross-linked starch, grafted starch, cyclodextrin, white dextrin, and dialdehyde starch; the acid-treated material includes at least one of formic acid, acetic acid, oxalic acid, malonic acid, and tartaric acid. The temperature control component is modified by acid treatment of starch. Modified starch is a good temperature control material. It hinders the hydration rate of tricalcium silicate by wrapping the action molecules on the surface of cement particles, thereby inhibiting the heat release of cement hydration. Modified starch can be gradually dissolved under alkaline conditions. Through acid treatment, the alkalinity around the starch molecules can be neutralized, thereby further slowing down the dissolution rate of modified starch, enhancing its action time, matching the hydration rate of tricalcium silicate, and thus improving the temperature control effect of the material.

[0030] The active component is prepared by mixing low-temperature alumina and CSH gel nanocrystalline core in a mass ratio of 1:2 to 1:4. CSH gel nanocrystalline core can improve the early density of concrete, and low-temperature alumina can improve the later density. The data show that the effect of the composite component on improving the density of concrete is far better than that of a single component, and it has a great relationship with the ratio of the two.

[0031] The self-healing component is prepared by mixing the accelerator and the main material in a ratio of 1:5 to 1:9; the main material is a silicate, including at least one of sodium silicate, potassium silicate, lithium silicate, and magnesium silicate; the accelerator is an aminocarboxylate, including at least one of sodium nitrilotriacetate, sodium ethylenediaminetetraacetate, and sodium diethylenetriaminepentacarboxylate. The main material is the main material that reacts chemically with water at the crack to generate crystals and plug the gap. The accelerator can react with the main material to further improve the effect of the main material.

[0032] The moisturizing component is commercially available ultra-fine rice husk ash with a specific surface area of ​​700m 2 / kg. Ultrafine rice husk ash can not only fill the pores, but its porous structure can also absorb some water and maintain the humidity inside the concrete, which plays an important role in reducing shrinkage and maintaining the hydration environment of the expansion components. At the same time, compared with high-performance water-absorbing resins, which have poor alkali resistance, negative impact on concrete strength, and high cost, this moisturizing material has a good application effect.

[0033] The plasticizing component is a mixture of vitrified microsphere powder and slump-retaining polycarboxylate water-reducing agent in a ratio of 4:1 to 9:1, wherein the product model of the polycarboxylate water-reducing agent is C900, and the water reduction rate is greater than 30%. The plasticizing component can effectively improve the adverse effects of the expansion component and the water-retaining component on the workability of the concrete, improve the workability and density of the concrete, and inhibit the generation of cracks in the concrete structure to a certain extent.

[0034] Adding self-healing temperature-controlling, anti-cracking and waterproof materials during the preparation of concrete is not only beneficial to the workability of the concrete mixture, but also can comprehensively improve the anti-cracking, waterproof and durability of the concrete structure from various aspects such as reducing the temperature rise inside the structure, weakening self-shrinkage, compensating for shrinkage, enhancing density and improving self-healing effect.

[0035] The preparation method of the self-healing temperature-controlling, anti-cracking and waterproof material for concrete of the present invention specifically comprises the following steps: uniformly mixing a carbonized modified magnesium oxide expansion agent, a carbonized modified calcium oxide-calcium sulfoaluminate expansion agent, an acidified modified starch, a low-temperature aluminum oxide, a CSH gel nanocrystalline core, a silicate, an aminocarboxylate, ultrafine rice husk ash, a vitrified microbead powder and a polycarboxylate water reducer in a certain proportion to obtain the self-healing temperature-controlling, anti-cracking and waterproof material.

[0036] Wherein, the preparation method of the carbonized modified magnesium oxide expansion agent is as follows:

[0037] (1) 1 kg of magnesium oxide expansion agent is placed in a steel crucible in a carbon dioxide atmosphere furnace;

[0038] (2) Adjust the motor speed to 750 rpm, raise the temperature to 400°C after 60 minutes, and start to introduce CO 2 -H2 O mixed gas and continued stirring at this temperature for 60 min;

[0039] (3) Stop ventilation, allow the furnace to cool naturally to room temperature, and pass the carbonized material through a 0.3 mm standard sieve to obtain a modified magnesium oxide expansion agent. The carbonization modification process of the calcium oxide-calcium sulfoaluminate expansion agent is the same as that of the calcium oxide-calcium sulfoaluminate expansion agent, except that the insulation temperature is 700°C and the fineness is controlled to be 0.08 mm to 0.2 mm.

[0040] The preparation method of modified starch by acidification treatment is as follows:

[0041] 500 g of modified starch was placed in a mixer at a speed of 300 rpm. At the same time, an acid material was sprayed and dripped at a rate of 0.05 ml / min for 120 min. Then the acid addition was stopped and the acid-modified material was obtained after continuous stirring for 24 h. Specific embodiment:

[0043] 1) Embodiment 1

[0044] The self-healing temperature-controlling, crack-resistant and waterproof material provided in this embodiment is formulated, by mass percentage, as follows: 60% expansion component, 2% temperature-controlling component, 8% active component, 8% self-healing component, 15% moisturizing component and 7% plasticizing component, wherein the expansion component is composed of carbonized modified magnesium oxide expansion agent and carbonized modified calcium oxide-calcium sulfoaluminate in a mass ratio of 1:1; the temperature-controlling component is acid-treated modified starch; the active component is composed of low-temperature alumina and CSH gel nanocrystalline core in a mass ratio of 1:3; the self-healing component includes sodium silicate and sodium ethylenediaminetetraacetate in a mass ratio of 1:7; the moisturizing component is ultrafine rice husk ash; and the plasticizing component is composed of vitrified microsphere powder and polycarboxylic acid water reducer in a mass ratio of 6:1.

[0045] 2) Embodiment 2

[0046] The self-healing temperature-controlling, crack-resistant and waterproof material provided in this embodiment has a formula of 70% expansion component, 2% temperature-controlling component, 6% active component, 5% self-healing component, 10% moisturizing component and 7% plasticizing component in terms of mass percentage, and the rest of the technical solutions are the same as those in Example 1.

[0047] 3) Embodiment 3

[0048] The self-healing temperature-controlling, crack-resistant and waterproof material provided in this embodiment has a formula of 50% expansion component, 3% temperature-controlling component, 10% active component, 10% self-healing component, 20% moisturizing component and 7% plasticizing component in terms of mass percentage, and the rest of the technical solutions are the same as those in Example 1.

[0049] 4) Embodiment 4

[0050] The self-healing temperature-controlling, crack-resistant and waterproof material provided in this embodiment has a formula of 50% expansion component, 1% temperature-controlling component, 10% active component, 10% self-healing component, 20% moisturizing component and 9% plasticizing component in terms of mass percentage, and the rest of the technical solutions are the same as those in Example 1.

[0051] 5) Comparative Example 1

[0052] The technical solution of the self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example is different from that of Example 1 in that the magnesium oxide is not subjected to carbonization modification treatment.

[0053] 6) Comparative Example 2

[0054] The self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example has a technical solution different from that of Example 1 in that calcium oxide-calcium sulfoaluminate is not subjected to carbonization modification and particle size optimization treatment, and a commercially available product is used.

[0055] 7) Comparative Example 3

[0056] The technical solution of the self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example is different from that of Example 1 in that the deformed starch is not treated with acid.

[0057] 8) Comparative Example 4

[0058] The technical solution of the self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example is different from that of Example 1 in that the active component adopts a single low-activity aluminum oxide.

[0059] 9) Comparative Example 5

[0060] The technical solution of the self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example is different from that of Example 1 in that no accelerator is added to the self-healing component.

[0061] 10) Comparative Example 6

[0062] The technical solution of the self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example is different from that of Example 1 in that the self-healing component is replaced by limestone powder.

[0063] 11) Comparative Example 7

[0064] The self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example has a technical solution different from that of Example 1 in that the moisturizing component adopts a conventional high-performance water-absorbing resin, and the water absorption rate of this material is 300 times in pure water and 60 times in alkaline solution.

[0065] 12) Comparative Example 8

[0066] The self-healing temperature-controlling, crack-resistant and waterproof material provided in this comparative example has a technical solution different from that of Example 1 in that the glass microbead powder in the plasticizing component is replaced by limestone powder.

[0067] The self-healing temperature-controlling, anti-cracking and waterproof materials prepared in the above Examples 1 to 4 and Comparative Examples 1 to 8 were subjected to performance tests, including: mortar hydration heat test and concrete working performance, mechanical properties, expansion performance, and secondary water permeability tests. The reference standards were industry standard JC / T2608-2021 "Concrete hydration temperature rise inhibitor", national standard GB / T 23439-2017 "Concrete expansion agent", national standard GB / T 50080-2016 "Ordinary concrete mixture performance test method standard", national standard GB / T 50081-2002 "Ordinary concrete mechanical properties test method standard" and GB 18445-2012 "Cement-based penetrating crystallization waterproof material", in which the mortar hydration heat experiment is based on 405 parts of benchmark cement, 1350 parts of standard medium sand, 45 parts of self-healing temperature-controlling and anti-cracking waterproof material, and 180 parts of mixing water, and the benchmark group benchmark cement is 450 parts, the mixing water is consistent, and no other materials are added; the concrete test is based on 260 parts of P·O 42.5 ordinary Portland cement, 50 parts of S95 mineral powder, 80 parts of Grade II fly ash, 720 parts of river sand, 1060 parts of crushed stone, 6.8 parts of water reducer, 160 parts of mixing water, and 30 parts of self-healing temperature-controlling and anti-cracking waterproof material, and the benchmark group is replaced by fly ash instead of the invented material.

[0068] The test results of the mortar hydration heat test of each embodiment and comparative example are shown in Table 1; the results of the concrete workability, mechanical properties and secondary water permeability are shown in Table 2; and the test results of the concrete expansion performance are shown in Table 3.

[0069] Table 1 Hydration heat test results of mortar with self-healing temperature-controlling and anti-cracking waterproof material

[0070]

[0071] It can be seen from Table 1 above that the 24h hydration heat reduction rate of the self-healing temperature-controlling anti-cracking waterproof material is more than 50%, but the 7d hydration heat reduction rate is not significantly affected, indicating that the material can inhibit the early hydration heat release of cement, but does not affect the later hydration heat, which also indirectly indicates that it will not have a negative impact on the later strength of concrete; from Comparative Examples 1 and 2, it can be seen that after the expansion component is carbonized, the hydration heat reduction rate is significantly improved. The reason is that after carbonization modification, the hydration activity of the expansion agent is inhibited and the influence of the early hydration heat release is reduced; Comparative Example 3 shows that after the modified starch is acidified, the 24h hydration heat reduction rate is increased from 38.5% to 51.2%, indicating that the scheme has a significant enhancing effect on the effect of the modified starch.

[0072] Table 2 Test results of concrete performance with self-healing temperature-controlling, crack-resistant and waterproof materials

[0073]

[0074] Table 2 above shows that the addition of the self-healing temperature-controlling, anti-cracking and waterproof material has a significant effect on the working performance, mechanical properties and self-repairing performance of concrete: the expansion degree is significantly increased and the collapse time is reduced, indicating that it is beneficial to the workability of concrete. Compared with the control group, the 7d compressive strength ratio is ≥105%, the 28d compressive strength ratio is ≥110%, the 60d compressive strength ratio is ≥110%, and the secondary water seepage pressure ratio exceeds 200%. Compared with Example 1, it can be seen from Comparative Example 1 that the magnesium oxide expansion agent can improve the secondary water permeability pressure after carbonization treatment, and it can be seen from Comparative Example 4 that after the active component is compounded, the compressive strength of concrete at all ages is significantly improved, and the water permeability pressure is also significantly improved. From Comparative Example 5, it can be seen that the self-healing promoter component can improve the secondary water permeability pressure, and from Comparative Example 6, it can be seen that the self-healing component can increase the water permeability pressure ratio from 140% to 260%. From Comparative Example 7, it can be seen that the high-performance water-absorbing resin will significantly reduce the workability and mechanical properties of concrete, and will affect the self-healing effect; from Comparative Example 8, it can be seen that the glass microspheres in the plasticizing component have a significant improvement on the workability of concrete. In addition, it can be seen from the above data that there is a certain synergistic effect between the functions of each component.

[0075] Table 3 Test results of expansion performance of concrete with self-healing temperature-controlling and crack-resistant waterproof materials

[0076]

[0077]

[0078] Table 3 above shows that: after adding the self-healing temperature-controlling anti-cracking waterproof material, the concrete specimen has a limited expansion rate of 0.025% after curing at 20°C for 14 days, which meets the technical index requirements of the post-casting strip, expansion reinforcement strip and other parts in JGJ / T 178-2009 "Technical Specifications for the Application of Shrinkage Compensating Concrete", and under the condition of 40°C water curing, the early expansion rate is low, but the later expansion rate continues to increase, which is mainly affected by the modification of the expansion component, which can extend the compensation shrinkage time and reduce the loss of early expansion energy under high temperature service environment. It can be seen from Comparative Examples 1 and 2 that compared with Example 1, the early expansion rate is improved, but the later expansion rate loss is large, especially under the condition of 40°C curing, which is more obvious, indicating that the modification treatment does reduce the loss of expansion energy of the expansion component in the plastic stage; from the 40°C expansion rate data of Comparative Example 3, it can be seen that the temperature control component has a certain promoting effect on the expansion energy release of the expansion agent under high temperature environment, indicating that there is a synergistic effect between the two.

[0079] It can be seen from Tables 1-3 above that the self-healing temperature-controlling, crack-resistant and waterproof material improves the workability and mechanical properties of concrete, increases the density of concrete structures, and can significantly reduce the hydration temperature rise, thereby reducing the risk of structural cracking by reducing the temperature shrinkage of concrete. At the same time, it can also extend the time of compensating for shrinkage, which is extremely beneficial for compensating for the shrinkage generated inside the structure during the cooling stage. The self-healing function it produces can greatly reduce the risk of structural cracks. Therefore, the material can comprehensively improve the crack resistance, waterproofness and durability of concrete structures from the above aspects.

[0080] Figure 1 The figure shows the development law of the restricted expansion rate of concrete specimens under 20°C and 40°C water curing conditions of the self-healing temperature-controlling, crack-resistant and waterproof material prepared in Example 1 of the present invention. From the data, it can be found that the material has a good shrinkage compensation effect, and under high-temperature curing conditions, the expansion rate maintains a continuous expansion characteristic, the expansion cycle is long, and it has a good shrinkage compensation effect on concrete at different ambient temperatures.

[0081] The content of the present invention is not limited to the embodiments listed, and any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the description of the present invention are covered by the claims of the present invention.

Claims

1. A self-healing temperature-controlling, anti-cracking and waterproof material for concrete, characterized in that: It includes 40% to 70% expansion component, 1% to 3% temperature control component, 5% to 10% active component, 5% to 10% self-healing component, 10% to 20% moisturizing component and 5% to 10% plasticizing component.

2. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 1, characterized in that: The expansion component consists of a carbonized modified magnesium oxide expansion agent and calcium oxide-calcium sulphoaluminate.

3. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 2, characterized in that: The temperature control component is prepared by acidification of modified starch, wherein the modified starch is at least one of oxidized starch, starch ester, starch ether, cross-linked starch, grafted starch, cyclodextrin, white dextrin, and dialdehyde starch; and the acid-treated material includes at least one of formic acid, acetic acid, oxalic acid, malonic acid, and tartaric acid.

4. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 3, characterized in that: The active component is prepared by uniformly mixing low-temperature alumina and CSH gel nano-crystal cores.

5. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 4, characterized in that: The self-healing component is prepared by uniformly mixing an accelerator and a main material in a ratio of 1:5 to 1:9; the main material is a silicate, including at least one of sodium silicate, potassium silicate, lithium silicate, and magnesium silicate; the accelerator is an aminocarboxylate, including at least one of sodium nitrilotriacetate, sodium ethylenediaminetetraacetate, and sodium diethylenetriaminepentacarboxylate.

6. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 5, characterized in that: The moisturizing component is ultra-fine rice husk ash.

7. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 6, characterized in that: The plasticizing component is a mixture of vitrified microsphere powder and polycarboxylic acid water reducer in a ratio of 4:1 to 9:

1.

8. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 7, characterized in that: It includes 15-35% of carbonized modified magnesium oxide expansion agent, 25-45% of carbonized modified calcium oxide-calcium sulfoaluminate expansion agent, 1-3% of acidified modified starch, 1-3% of low-temperature aluminum oxide, 4-8% of CSH gel nanocrystalline core, 4.5-9% of sodium silicate, 0.5-1.5% of sodium ethylenediaminetetraacetate, 10-20% of ultrafine rice husk ash, 3.5-8% of vitrified microsphere powder and 0.5-2% of polycarboxylic acid water reducer.

9. The self-healing temperature-controlling, crack-resistant and waterproof material for concrete according to claim 8, characterized in that: It includes 25% carbonized modified magnesium oxide expander, 35% carbonized modified calcium oxide-calcium sulfoaluminate expander, 2% acidified modified starch, 2% low-temperature alumina, 5% CSH gel nanocrystalline core, 6% sodium silicate, 1% sodium ethylenediaminetetraacetate, 15% ultrafine rice husk ash, 8% vitrified microsphere powder and 1% polycarboxylic acid water reducer.

10. The method for preparing any one of the self-healing temperature-controlling, crack-resistant and waterproof materials for concrete according to claims 1-9, characterized in that: A self-healing temperature-controlling, anti-cracking and waterproof material is obtained by uniformly mixing carbonized modified magnesium oxide expansion agent, carbonized modified calcium oxide-calcium sulfoaluminate expansion agent, acidified modified starch, low-temperature alumina, CSH gel nanocrystalline core, silicate, aminocarboxylate, ultrafine rice husk ash, vitrified microbead powder and polycarboxylate water reducer in a certain proportion.

Citation Information

Patent Citations

  • Self-healing inorganic nano anti-cracking permeability reducing agent and preparation method thereof

    CN116514451A

  • Self-healing anti-freezing rust-inhibiting anti-cracking agent as well as preparation method and application thereof

    CN116621499A

Cited By

  • Quality detection and risk assessment method of aggregate for bridge concrete mixing

    CN121410247A

  • Plateau alpine region concrete anti-cracking admixture as well as preparation method and application thereof

    CN121426466A